Scrambling and Reorientation of Classical Atmospheric Boundary Layer Turbulence in Hurricane Winds. Issue 7 (9th April 2021) - Momen, Mostafa; Parlange, Marc B.; Giometto, Marco G.
Abstract: The societal, economic, and ecosystem consequences of hurricanes are projected to increase with ocean warming. Although wind gusts can be highly destructive in these extreme events, current knowledge on hurricane turbulence structures is limited due to insufficient measurement sampling data and the low resolution (1–5 km) of weather models. To bridge this knowledge gap, we propose and validate a numerical approach based on a novel theoretical framework that enables us to simulate hurricane boundary layer (BL) at ≈25 m resolution. Our high‐resolution simulations revealed an intermediate layer in the hurricane BL in which the streamwise‐elongated coherent turbulence structures that typically populate the BL flows are broken into smaller eddies. The distinctive structure of turbulence in cyclonic winds also alters internal BL dynamics during hurricane landfalls by reorienting the roll vortices. We demonstrate that the centrifugal forces in hurricanes cause scrambling and reorientation of the elongated conventional atmospheric BL streaks. Plain Language Summary: Hurricanes have been the costliest natural disasters in US history. Understanding the hurricane wind structure is critical to quantify the impact of these storms on built and natural environments. Current knowledge about turbulent motions in cyclonic winds, however, is limited due to the coarse grid stencil of weather models and insufficient observational sampling data. Here, we bridge this knowledge gap and identify a turbulence regime that is unique to hurricane winds. We show that over a layer of the atmosphere, relevant to the wind‐engineering applications, hurricanes break the streamwise‐elongated streaks that commonly populate atmospheric turbulence into tilted and smaller structures. We show that the change in the orientation of turbulent eddy structures and shifting of the energy spectrum toward higher wave numbers are associated with the centrifugal forces in hurricanes. Key Points: A novel large‐eddy simulation framework is developed and used to study mean flow and turbulence structures in hurricane boundary layers In hurricane flows, energy in the power spectrum is shifted toward higher wavenumbers, and large coherent turbulence structures break down A two‐point correlation analysis reveals reorientation and scrambling of conventional streamwise streaks due to centrifugal forces